Academic stress in students of public and global health and health administration careers during the COVID-19 pandemic - Espino-Sulca, Jean Marco (2025)
Objective: To evaluate the level of academic stress among students in the public health, global health, and health administration programs at a Peruvian university during the COVID-19 pandemic. Methods: A quantitative, observational, cross-sectional study was performed with a sample of 126 third- and fourth-year students from these programs. All students were invited to participate via institutional email. Academic stress levels were assessed using the SISCO Inventory of Academic Stress through Google Forms after obtaining informed consent. Results: 89 students who completed the questionnaire were included. 95.5% reported experiencing feelings of nervousness and worry throughout the semester. Among these, 55 (64.7%) experienced severe stress, 20 (23.5%) moderate stress, and 10 (11.8%) mild stress. Conclusion: Students in the Public and Global Health and Health Administration programs at this Peruvian university experienced different levels of academic stress during the COVID-19 pandemic, with severe stress being the most common, followed by moderate and mild levels.